The Horseshoe Crab - Jami McLaughlin; Frans Lanting; David Griffis; Martin B. Main (EDIS)
This document is WEC182, one of a series of the Wildlife Ecology and Conservation Department, UF/IFAS Extension. Original publication date September 2004. This brochure was developed as a product of the Florida Master Naturalist Program and reviewed by the Florida Fish and Wildlife Commission, Florida Marine Research Institute.